NEUE MUSIK IN AFRIKA, ASIEN UND OZEANIEN. DISKOGRAPHIE UND HISTORISCH- STILISTISCHER UBERBLICK (New music in Africa, Asia and Oceania. Discography and historical and stylistic survey), by Wolfgang Laade, published by the author, Heidelberg, 1971. GEGENWARTSFRAGEN DER MUSIK IN AFRIKA UND ASIEN, eine grundlegende Bibliographic (Contemporary enquiries into the music of Africa and Asia, a basic bibliography), by Wolfgang Laade, Verlag Valentin Koerner, Baden-Baden, 1971 - Nurse, G. T. (International Library of African Music, 1971)
pages: 98-99
Keywords: African Music